Development and application of two closed-loop systems for automatic early warning of thrombus based on AI (基于AI的血栓自动预警两闭环系统的开发与应用) - LI Lin (李琳); YANG Li (杨丽); HE XiaoHong (何晓红); ZHOU Ziyuan (周子源); YAN Guanli (闫观丽) (Journal of International Translational Medicine Limited, 2023)
Objective To develop and apply artificial intelligence-based (AI-based)two closed-loop systems for automatic early warning of thrombosis, in order to improve the work efficiency of medical staff and reduce the incidence of venous thromboembolism (VTE) in hospitalized patients. Methods A total of 47148 inpatients in the hospital from January 2020 to December 2020 were selected as the control group, and 95184 patients from January 2021 to December 2021 were selected as the observation group. The control group used routine computer systems to evaluate and implement prevention programs. The AI-based automatic thrombus early warning and two closed-loop systems were used for evaluation and intervention in the observation group. The accuracy of VTE risk assessment, time spent on evaluation, implementation rate of basic, physical and drug prevention, VTE-related inspection rate, and VTE incidence were compared between the two groups. Results Compared with the control group, the accuracy rate of VTE risk assessment, the implementation rates of basic, physical and drug prevention, the rate of VTE-related examinations and proportion of patients with time spent on evaluation less than 1 minutes in the observation group were significantly increased (P<0. 01), and the incidence of VTE was significantly decreased (P<0. 01). Conclusion The AI-based two closed-loop systems for automatically thrombus warning may help medical workers improve work efficiency, improve the execution rate of basic, physical and drug prevention, increase VTE-related inspection rates, and reduce VTE incidence. (目的 开发并应用基于AI的血栓自动预警两闭环系统, 提高医护人员工作效率, 降低住院患者静脉血栓栓塞症(VTE)发生率。方法 选取医院2020年1月-12月住院患者47148例为对照组, 2021年1月-12月95184例患者为观察组。对照组使用传统计算机系统评估并实施预防方案, 观察组使用基于AI的血栓自动预警两闭环系统(医-护-患闭环, 人防-物防-技防)进行评估与干预。比较两组VTE风险评估准确率、评估时间、基础预防的执行率、物理预防的执行率、药物预防执行率、VTE相关检查率和VTE发生率。结果 与对照组相比, 观察组VTE风险评估准确率、基础预防执行率、物理预防执行率、药物预防执行率、VTE相关检查率和评估时间＜1 min的患者比例提高(P＜0. 01), VTE发生率降低(P＜0. 01)。结论 基于AI的血栓自动预警两闭环系统通过医护患闭环、人防物防技防闭环, 帮助医护工作者提高了工作效率, 提升基础、物理、药物预防的执行率, 加大VTE相关检查率, 降低VTE发生率。)